ANALYSIS AND DESIGN OF USER INTERFACE/USER EXPERIENCE WITH THE DESIGN THINKING METHOD IN THE ACADEMIC INFORMATION SYSTEM OF JENDERAL SOEDIRMAN UNIVERSITY - Hananda Ilham; Bangun Wijayanto; Swahesti Puspita Rahayu (Informatika, Universitas Jenderal Soedirman, 2021)
User Interface/User Experience (UI/UX) design is very important because with a good design that meets user needs, it can make users feel comfortable when using a product. One example is the Academic Information System (SIA), if the design of the SIA is not user friendly, it will have an impact on both the user and the system. Such as input errors, missing information, difficulties in using it. The purpose of conducting UI / UX analysis and design at SIA Universitas Jenderal Soedirman is to solve the problems experienced by users today. Users involved in this research are students. Design is made using the Design Thinking method and for the testing using Usability Testing.